2005
DOI: 10.1659/0276-4741(2005)025[0244:ioglad]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Grazing Livestock and Distance from Water Source on Soil Fertility in Southern Mongolia

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 18 publications
6
86
0
Order By: Relevance
“…Many studies proved that livestock density (i.e., grazing pressure) is usually highest close to water sources or settlements and decreases with distance away from such localities (Andrew and Lange, 1986;FernandezGimenez and Allen-Diaz, 2001;Landsberg et al, 2003;Sasaki et al, 2008;Cheng et al, 2011). According to Stumpp et al (2005) the livestock spatial densities were higher in the first 300 m of the transects from the local centers. This finding of the heavy grazing with a radial gradient was also found at our study site (Cheng et al, 2011), which spots a trampling-active area.…”
Section: Experimental Area Settingmentioning
confidence: 99%
“…Many studies proved that livestock density (i.e., grazing pressure) is usually highest close to water sources or settlements and decreases with distance away from such localities (Andrew and Lange, 1986;FernandezGimenez and Allen-Diaz, 2001;Landsberg et al, 2003;Sasaki et al, 2008;Cheng et al, 2011). According to Stumpp et al (2005) the livestock spatial densities were higher in the first 300 m of the transects from the local centers. This finding of the heavy grazing with a radial gradient was also found at our study site (Cheng et al, 2011), which spots a trampling-active area.…”
Section: Experimental Area Settingmentioning
confidence: 99%
“…Distance-dependent effects including declines in perennial plants and species richness as well as structural diversity of perennial plants have been observed (Brooks et al 2006;Landman et al 2012). Further, their influence on soil nutrients (Stumpp et al 2005), landscape degradation (James et al 1999), soil compaction and erosion (Mugerwa et al 2014), and variation in biomass defoliation and trampling (Shahriary et al 2012) has been observed. Also, changes in forage species composition with increased presence of unpalatable perennial shrubs beyond the zone of extreme degradation coupled with a decrease in the abundance of palatable native perennial grasses have been documented (James et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…As such, defecation and urination by these animals could have enhanced nutrient deposition and accumulation leading to soil organic carbon and nitrogen augmentation. Stumpp et al (2005) reported high dung deposits around the Mongolian piospheres. Smet and Ward (2006) and Shahriary et al (2012) also reported high soil organic carbon and total nitrogen around the piospheres of South Africa and Iran, respectively.…”
Section: Soil Organic Carbon and Total Nitrogenmentioning
confidence: 99%